Consumer Protection and Financial Literacy : Lessons from Nine Country Studies - Rutledge, Susan L. (2012)
The recent turmoil in financial markets worldwide has emphasized the need for adequate consumer protection and financial literacy for long-term stability of the financial sector. This Working Paper aims to summarize key lessons from reviews of consumer protection and financial literacy in nine middle-income countries of Europe and Central Asia (Azerbaijan, Bulgaria, Croatia, the Czech Republic, Latvia, Lithuania, Romania, the Russian Federation and Slovakia). All the country assessments used a systematic common approach, based on a set of Good Practices for Consumer Protection and Financial Literacy developed by the World Bank's Europe and Central Asia Region. The objective of the Working Paper is to contribute to the international dialog on strengthening financial consumer protection and financial literacy in emerging markets.A financial consumer protection regime should meet three objectives. First, consumers should receive accurate, simple, comparable information of a financial service or product, before and after buying it. Second, consumers should have access to expedient, inexpensive and efficient mechanisms for dispute resolution with financial institutions. Third, consumers should be able to receive financial education when and how they want it. A common challenge among the nine countries is the need of an adequate institutional structure for financial consumer protection. However independent of the specific institutional structures, financial consumers should have one single agency where to submit complaints and inquiries. Financial institutions should be required to apply fair, non-coercive and reasonable practices when selling and advertising financial products and services to consumers. Personal data should also be carefully protected.